2017
DOI: 10.2519/jospt.2017.7682
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility in Adolescent Athletes: Pain, Functional Ability, Quality of Life, and Musculoskeletal Injuries

Abstract: U t STUDY DESIGN:Cross-sectional. U t BACKGROUND:Generalized joint hypermobility (GJH) may increase pain and likelihood of injuries and also decrease function and health-related quality of life (HRQoL) in elite-level adolescent athletes. U t OBJECTIVE:To assess the prevalence of GJH in elite-level adolescent athletes, and to study the association of GJH with pain, function, HRQoL, and musculoskeletal injuries. U t METHODS:A total of 132 elite-level adolescent athletes (36 adolescent boys, 96 adolescent girls; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
(43 reference statements)
5
28
0
1
Order By: Relevance
“…However, the findings of the current study were consistent with results of earlier studies in adolescents and adults with asymptomatic GJH compared to non-hypermobile controls (Clinch et al, 2011;Jensen et al, 2013;Junge et al, 2015;Mebes et al, 2008). In addition, a recent study also showed that no differences in physical functioning, measured as lower extremity function and motor performance, occurred between adolescent athletes with asymptomatic GJH and non-hypermobile adolescent athletes (Schmidt et al, 2017). A possible explanation between the different outcomes of PAL could be that the current study and Clinch et al (2011) used accelerometry as objective measurement, whereas Scheper et al (2014a) used a subjective measure.…”
Section: Discussionsupporting
confidence: 92%
“…However, the findings of the current study were consistent with results of earlier studies in adolescents and adults with asymptomatic GJH compared to non-hypermobile controls (Clinch et al, 2011;Jensen et al, 2013;Junge et al, 2015;Mebes et al, 2008). In addition, a recent study also showed that no differences in physical functioning, measured as lower extremity function and motor performance, occurred between adolescent athletes with asymptomatic GJH and non-hypermobile adolescent athletes (Schmidt et al, 2017). A possible explanation between the different outcomes of PAL could be that the current study and Clinch et al (2011) used accelerometry as objective measurement, whereas Scheper et al (2014a) used a subjective measure.…”
Section: Discussionsupporting
confidence: 92%
“…Because of this, we hypothesised that part of the reason for the increased risk of ACL injury, seen in females, could be attributed to hypermobility. However, in females, other possible risk factors, such as reduced neuromuscular control,47–50 a narrow femoral notch4 51 or hormonal factors, could be of greater significance 52…”
Section: Discussionmentioning
confidence: 99%
“…However, these sway variables are not commonly used to assess sway and appear to have been used in only one previous study by this same group (Thewlis et al, 2014). By contrast, COP path length is routinely used to assess postural sway, with numerous published studies employing this measure to quantify sway in just the last calendar year (Clark et al, 2017;Howard et al, 2017;Kalron 2017;Koyama and Yamauchi 2017;Lee and Brown 2017;Ludwig 2017;Pavao et al, 2017;Schmidt et al, 2017;Scholes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%